2012
DOI: 10.1002/anie.201201160
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Solid‐State NMR Spectroscopy of Protein in Heterogeneous Membranes: The Baseplate Antenna Complex of Chlorobaculum tepidum

Abstract: A clever combination: an in situ solid-state NMR analysis of CsmA proteins in the heterogeneous environment of the photoreceptor of Chlorobaculum tepidum is reported. Using different combinations of 2D and 3D solid-state NMR spectra, 90 % of the CsmA resonances are assigned and provide on the basis of chemical shift data information about the structure and conformation of CsmA in the CsmA-bacteriochlorophyll a complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…The in-situ NMR experiments may also serve as a steppingstone toward structural characterization of LHC pigment-protein complexes in their native environment. While in-cell or in-situ NMR spectroscopy for structure characterization is very challenging, several studies have been reported, for example solid-state NMR of recombinant-expressed PagL in E. coli whole cells and cell envelopes, in-situ NMR of the Chl-binding CsmA protein and Dynamic NuclearPolarization NMR of proteins in native cellular membranes[59][60][61]. In-cell NMR studies that are aimed at structural characterization of a target protein generally rely on genetic manipulation to reduce the background signals of other cellular or membrane components.…”
mentioning
confidence: 99%
“…The in-situ NMR experiments may also serve as a steppingstone toward structural characterization of LHC pigment-protein complexes in their native environment. While in-cell or in-situ NMR spectroscopy for structure characterization is very challenging, several studies have been reported, for example solid-state NMR of recombinant-expressed PagL in E. coli whole cells and cell envelopes, in-situ NMR of the Chl-binding CsmA protein and Dynamic NuclearPolarization NMR of proteins in native cellular membranes[59][60][61]. In-cell NMR studies that are aimed at structural characterization of a target protein generally rely on genetic manipulation to reduce the background signals of other cellular or membrane components.…”
mentioning
confidence: 99%
“…Solid-state NMR spectroscopy is becoming an increasingly important tool for the atomic scale investigation of biological macromolecules in complex heterogenous environment, including protein complexes, amyloid fibrils, and membrane proteins [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. The growing capability of the method is ascribed to development of high-field instrumentation, fast sample spinning probes, new isotope-labelling procedures, and design of efficient pulse sequences for manipulating the spins to ensure high resolution and establishment of structural parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Lately, the potential of solid-state NMR has been exemplified by studies of fascinating heterogeneous systems such as bacteriorhopsin (bR) in purple membranes, 8,9 GvpA proteins in collapsed gas vesicles, 10,11 PagL in native Escherichia coli membranes, 12 and the photosynthetic antenna protein, CsmA, from a phototrophic prokaryote in native chlorosome organelles. 13 In the most common form, biological solid-state NMR takes advantage of magic-angle-spinning (MAS) to average anisotropic nuclear spin interactions to first order and thereby enable detection of high-resolution spectra from which signals can be assigned. To support assignment and establish internuclear distance constraints such experiments are typia) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…ncn@inano.au.dk cally combined with dipolar recoupling methods selectively reintroducing dipole-dipole coupling interactions between spins being incorporated through isotope labeling (typically 13 C, 15 N) or in natural abundance (typically 1 H). When operating with recoupling among selectively or sparsely incorporated spin isotopes, dipolar recoupling may provide accurate distances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation